Characterization of fatigue damages in composite laminates using Lamb wave velocity and prediction of residual life. (15th April 2017) - Tao, Chongcong; Ji, Hongli; Qiu, Jinhao; Zhang, Chao; Wang, Zhan; Yao, Weixing
Abstract: In this paper, the S0 -mode Lamb wave phase velocity at low frequency range is chosen to characterize fatigue damages accumulated in composite laminates under cyclic loadings. A stiffness/velocity degradation model is proposed based on three distinctive damage mechanisms: fiber breaks, matrix cracks and delamination, all of which are always involved in fatigue damage process. In order to reduce the complexity of the damage model, fiber damage is treated as an independent damage and delamination is coupled with matrix cracks. An approximation of shear-lag model is then proposed to avoid any direct measurements of crack density for it is highly impractical in real applications. Following this, energy release rate for formation of matrix cracks is extracted based on measured phase velocity and damage evolution is realized by incorporating a modified Paris law. Controlled fatigue experiments were conducted where in-situ phase velocity was measured by a laser ultrasonic system. The fatigue damages were then characterized using the proposed damage model with the measured velocity. Finally, the ability of proposed model to predict residual lives was also validated and good accuracy has been obtained.